2022
DOI: 10.1111/apt.17222
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of adding on or switching to peginterferon α‐2b in HBeAg‐positive chronic hepatitis B patients with long‐term entecavir treatment: a multicentre randomised controlled trial

Abstract: Background & Aims:The strategies of adding on or switching to peginterferon (PEG-IFN) improved the serological response rates in patients with chronic hepatitis B (CHB) who had previously experienced treatment with nucleos(t)ide analogues. However, robust data on which combination strategy is more effective remain lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Secondly, as mentioned in the former that the actual mechanism of CXCL13 _rs76084459 in relation to PegIFNα treatment response has not been revealed in this study, which is warranted to be further investigated in the future. Thirdly, some researchers have found that various strategies combining NUCs and PegIFNα may increase the rate of HBsAg loss, 39–41 but in this article, most of the patients in Cohort 1 and all the patients in Cohort 2 received PegIFNα monotherapy, only a small part of patients in Cohort 1 received PegIFNα along with NUCs therapy (arm D, n = 57), it is insufficient to assess whether the HBsAg loss rate affected by treatment strategies or CXCL13 _rs76084459 genotypes since only a few patients reached HBsAg loss at the end of follow‐up. However, we found that not only in patients received PegIFNα monotherapy (arm A, B, and C) but also in patients received PegIFNα along with NUCs therapy (arm D), the CR rates were constantly higher in patients with the GT/TT genotype than those in patients with the GG genotype at week 72, though the difference did not reach significant level due to the relatively small sample size in every subgroups of Cohort 1 (Figure ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Secondly, as mentioned in the former that the actual mechanism of CXCL13 _rs76084459 in relation to PegIFNα treatment response has not been revealed in this study, which is warranted to be further investigated in the future. Thirdly, some researchers have found that various strategies combining NUCs and PegIFNα may increase the rate of HBsAg loss, 39–41 but in this article, most of the patients in Cohort 1 and all the patients in Cohort 2 received PegIFNα monotherapy, only a small part of patients in Cohort 1 received PegIFNα along with NUCs therapy (arm D, n = 57), it is insufficient to assess whether the HBsAg loss rate affected by treatment strategies or CXCL13 _rs76084459 genotypes since only a few patients reached HBsAg loss at the end of follow‐up. However, we found that not only in patients received PegIFNα monotherapy (arm A, B, and C) but also in patients received PegIFNα along with NUCs therapy (arm D), the CR rates were constantly higher in patients with the GT/TT genotype than those in patients with the GG genotype at week 72, though the difference did not reach significant level due to the relatively small sample size in every subgroups of Cohort 1 (Figure ).…”
Section: Discussionmentioning
confidence: 92%
“…It should be pointed out that, though HBsAg loss is an ideal efficacy endpoint for assessment of HBV treatment, there were only a few patients in the two PegIFNα cohorts of our study achieved the loss of HBsAg and the sample size is insufficient to analyze the relationship between CXCL13_rs76084459 and HBsAg loss. We believe that more patients enrolled in the future will help the evaluation of this indicator.HBsAg loss,[39][40][41] but in this article, most of the patients in Cohort 1 and all the patients in Cohort 2 received PegIFNα monotherapy, only a small part of patients in Cohort 1 received PegIFNα along with NUCs therapy (arm D, n = 57), it is insufficient to assess whether the HBsAg loss rate affected by treatment strategies or CXCL13_rs76084459 genotypes since only a few patients reached HBsAg loss at the end of follow-up. T A B L E 4 a Baseline level.b…”
mentioning
confidence: 89%
“…Pegylated interferon (Peg-IFN) offers advantages over nucleoside analogs (NAs), including shorter treatment durations, higher HBeAg seroconversion/HBsAg loss rates, and better post-treatment immune control in HBeAg-positive patients [ 138 ]. However, Peg-IFN therapy often comes with adverse side effects.…”
Section: Potential Applications Of Exosomes In Hepatitis Bmentioning
confidence: 99%